Missbrauch des Beweisantragsrechts im Strafprozess und Missbrauchsabwehr. - Liu, Chang (Schriften zum Prozessrecht, 2021)
»Abuse of the Right to Apply for Evidence to Be Taken in Criminal Proceedings and the Prevention of Abuse« The right to apply for evidence to be taken has been restricted in recent years in the name of the fight against abuse of this right, which raises the question of when this right is abused and how far the anti-abuse measures may go. This work examines the purpose of this right and categorizes on this basis abusive behaviors into several groups. Since all sorts of abuse of this right can be prevented by existing means, the recently introduced anti-abuse methods are superfluous, they even bring new risks of abuse.